Measuring Well-Being: W3 Indicators to Complement GDP - Marco Giesselmann; Richard Hilmer; Nico A. Siegel; Gert G. Wagner (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2013)
Numerous people in Germany, including politicians and researchers, believe that the gross domestic product (GDP) is an outdated indicator of a society's prosperity. Therefore, at the end of 2010, the German Bundestag, the federal parliament, established a study commission (Enquete-Kommission) tasked with developing an alternative to the GDP for measuring growth, prosperity, and quality of life. This commission has now submitted a proposal: to supplement the GDP with nine additional indicators, including a wide range of factors such as the distribution of income, biodiversity, and life expectancy. The ten indicators cover three dimensions of well-being - economy, ecology, and social wealth - and hence are called W3 Indicators. Replacing the gross domestic product by a single alternative index was rejected by the commission, however, since it is not possible to reduce citizens' very different wishes and expectations to a common denominator. A representative survey of registered voters conducted by DIW Berlin and TNS Infratest shows that citizens consider the indicators proposed by the commission to be important. Respondents ranked preserving democracy and freedom as the most relevant indicator and further increasing life expectancy as the least relevant. The average per capita income - as an indicator of the gross domestic product - is the second least relevant factor as far as registered voters in Germany are concerned. However, the study also shows that opinions on the importance of different indicators vary widely. Moreover, there are systematic differences in the relevance of various policy areas for different social groups.
Keywords: B59; D63; H11; I32; Z18; 330; GDP; GDP and beyond; quality of life; Germany; TNS Infratest; SOEP; W3 Indicators